2018
DOI: 10.1038/s41598-018-35611-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanofocusing of X-ray free-electron laser using wavefront-corrected multilayer focusing mirrors

Abstract: A method of fabricating multilayer focusing mirrors that can focus X-rays down to 10 nm or less was established in this study. The wavefront aberration induced by multilayer Kirkpatrick–Baez mirror optics was measured using a single grating interferometer at a photon energy of 9.1 keV at SPring-8 Angstrom Compact Free Electron Laser (SACLA), and the mirror shape was then directly corrected by employing a differential deposition method. The accuracies of these processes were carefully investigated, considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…The correction introduced by a suitable scheme converts an aberrated optics to pseudo-perfect optics which otherwise prevents achieving diffraction-limited focusing. A few schemes such as active bimorph mirrors (Mimura et al, 2010), refractive correctors (Sawhney et al, 2016;Seiboth et al, 2017), invariable-multilayer deposition (Matsuyama et al, 2018), diffractive wavefront correction (Probst et al, 2020) and layer stress controlling method (Cheng & Zhang (2019) have been demonstrated as tools for phase error corrections of different X-ray optical elements. Refraction-based correctors are thin, easy to insert into the beam path, do not change the optical axis and are straightforward to align.…”
Section: Introductionmentioning
confidence: 99%
“…The correction introduced by a suitable scheme converts an aberrated optics to pseudo-perfect optics which otherwise prevents achieving diffraction-limited focusing. A few schemes such as active bimorph mirrors (Mimura et al, 2010), refractive correctors (Sawhney et al, 2016;Seiboth et al, 2017), invariable-multilayer deposition (Matsuyama et al, 2018), diffractive wavefront correction (Probst et al, 2020) and layer stress controlling method (Cheng & Zhang (2019) have been demonstrated as tools for phase error corrections of different X-ray optical elements. Refraction-based correctors are thin, easy to insert into the beam path, do not change the optical axis and are straightforward to align.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the influence on the beam profile near the focus caused by misalignments, as well as tolerances. To simplify the calculation, we used a lens model [refer to Matsuyama et al (2018) for more details on parameters], which consists of a pair of one-dimensional lenses with a numerical aperture of 0.01 and focal length of 70 mm that are orthogonally arranged with each other. The wavefields around the focus were calculated by changing the distance from the focus Áz (i.e.…”
Section: Relationship Between Mirror Misalignments and Beam Profilementioning
confidence: 99%
“…For higher intensities of up to 10 22 W cm À2 , a multilayer KB mirror system (Mimura et al, 2010;Cesar et al, 2017) has been developed to focus XFEL beams of less than 10 nm using a larger numerical aperture than that achieved with the totalreflection KB mirrors. To fabricate the multilayer KB mirrors with a /4 wavefront accuracy, an ultraprecise shape-correction technique, which involves shape-error determination with wavefront sensing (Rutishauser et al, 2011;Matsuyama et al, 2012;Kayser et al, 2017;Inoue, Matsuyama et al, 2018) and shape-correction with differential deposition at subnanometre accuracy (Ice et al, 2000;Handa et al, 2008), has been developed (Matsuyama et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, new refractive optical elements for aberration correction (Sawhney et al, 2016;Seiboth et al, 2017;Laundy et al, 2019) and wavefront manipulation (Seiboth et al, 2019) have emerged. They provide an alternative to deformable mirrors (Mimura et al, 2010) and differential deposition methods (Matsuyama et al, 2018) for wavefront correction as well as to diffractive elements (Vila-Comamala et al, 2014;Loetgering et al, 2020) for wavefront manipulation.…”
Section: Introductionmentioning
confidence: 99%